Predictive Threshold Value of the Breathing Reserve for the Decline in Cardiorespiratory Fitness Among the Healthy Middle-Aged Population - Tao Shen; Yang Wang; Jinglin Li; Shunlin Xu; Peng Wang; Wei Zhao (Journal of Cardiovascular Development and Disease)
Objective: To investigate the cut-off value of the breathing reserve for predicting a decline in cardiorespiratory fitness (CRF) among healthy middle-aged Chinese individuals. Methods: Healthy middle-aged individuals who underwent cardiopulmonary exercise testing (CPET) at the Peking University Third Hospital from May to October 2021 were selected. The study included 321 participants, with an average age of 48.8 ± 5.7 years. They were divided into two groups based on the peak oxygen uptake (VO2peak): the adequate CRF group and the CRF decline group. Multivariate logistic regression analysis was used to explore the factors influencing CRF. Results: In the male CRF decline group, heart rate, alanine aminotransferase, end-tidal partial pressure of carbon dioxide (PETCO2), and breathing reserve (BR%) were significantly higher, while the oxygen uptake at the anaerobic threshold (VO2@AT) was lower. An elevated BR% was independently associated with CRF decline (OR = 1.111, 95% CI: 1.068–1.156). The female CRF decline group had significantly higher FEV1/FVC and BR% and significantly lower age, fasting glucose, hemoglobin, and VO2@AT compared to the adequate CRF group. Elevated BR% was independently associated with CRF decline (OR = 1.086, 95% CI: 1.038–1.137). The receiver operating characteristic (ROC) curve for the males showed an area under the curve (AUC) of 0.769 (95% CI: 0.703–0.827) with an appropriate BR% cut-off value of 49.9%, sensitivity of 59.9%, and specificity of 77.8%. For the females, the ROC curve displayed an AUC of 0.694 (95% CI: 0.607–0.773) with an appropriate BR% cut-off value of 57.0%, sensitivity of 58.7%, and specificity of 86.0%. Conclusions: The breathing reserve was independently associated with CRF. The appropriate cut-off values for BR% to predict CRF decline were 49.9% for the males and 57.0% for the females.